2006
DOI: 10.1111/j.1750-3841.2006.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐Lowering Effect of Eriocitrin, the Main Flavonoid in Lemon Fruit, in Rats on a High‐Fat and High‐Cholesterol Diet

Abstract: Eriocitrin (eriodictyol 7‐O‐β‐rutinoside) is the main flavonoid in lemon fruit. In this study, eriocitrin was investigated for its lowering effect on serum and hepatic lipids in high‐fat and high‐cholesterol fed rats. Rats in the control group (N= 6) were fed a 20% lard and 1% cholesterol diet for 21 d, and rats in the 0.35% eriocitrin group (N= 6) and 0.70% eriocitrin group (N= 6) were fed a diet supplemented with eriocitrin 0.35% and 0.70%, respectively. The content of hepatic total cholesterol and triglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 21 publications
(27 reference statements)
0
41
0
Order By: Relevance
“…2). Miyake et al (2006) investigated the hypolipidemic effects of eriocitrin, the main flavonoid in lemon fruit, and their observation indicates that eriocitrin can increase faecal bile acid and cholesterol outputs. Besides, the hypocholesterolemic effect of flaxseed oil was associated with the up-regulation of plasma cholesterol clearance (LDL receptor expression), and an increase of faecal cholesterol excretion (Tzang et al, 2009).…”
Section: Changes Of Serum Lipids and Cholesterol Profile As Well As mentioning
confidence: 99%
“…2). Miyake et al (2006) investigated the hypolipidemic effects of eriocitrin, the main flavonoid in lemon fruit, and their observation indicates that eriocitrin can increase faecal bile acid and cholesterol outputs. Besides, the hypocholesterolemic effect of flaxseed oil was associated with the up-regulation of plasma cholesterol clearance (LDL receptor expression), and an increase of faecal cholesterol excretion (Tzang et al, 2009).…”
Section: Changes Of Serum Lipids and Cholesterol Profile As Well As mentioning
confidence: 99%
“…Eriocitrin was shown to bind weakly to the oestrogen receptor, ERb, displacing 2,4,6,7-[ 3 H]17-boestradiol (Verhoog et al, 2007b) and would therefore contribute to the putative phytoesterogenicity of Cyclopia extracts. The antioxidant and lipid-lowering effects of eriocitrin (Miyake et al, 2006) could contribute to the health-promoting properties of these herbal teas. Its reliable quantification is therefore important for characterisation of extracts used for bioactivity testing and development of nutraceutical extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Our hesperidin results were in harmony with the Caristi et al (2003) findings. However; other researchers indicated that eriocitrin (eriodictyol 7-O-β-rutinoside) was the main flavonoid in lemon fruit (Tripoli et al 2007;Miyake et al 2006). GonzalezMolina et al (2012) studied on new beverages of lemon juice (Fino) with elderberry and grape concentrates as a source of bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%